Experiencer Construction in Indonesian - Zikriani; Mulyadi; Muhammad Yusuf (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the morphosyntactic realization of experiencer constructions in Indonesian using corpus-based data. A qualitative analysis was conducted on 500 clauses collected from the Indonesian CQPweb corpus and spoken data from YouTube. Applying distributional analysis and the X-Bar framework, the study investigates how experiencers and stimuli are structurally encoded across different verb classes. The findings reveal three major construction types: experiencer as subject, experiencer as object, and datival experiencer. These constructions systematically correlate with psychological verb classes and display variation in argument realization. Indonesian encodes experiencer roles through syntactic position and prepositional marking rather than morphological case. This research provides the first systematic corpus-based account of Indonesian experiencer constructions and contributes to broader discussions on argument structure and semantic role mapping in Austronesian languages.